The Role of Joint Liability in Lowering The Risk of Farmer and Agriculture Crowdfunding (A case study of one agriculture crowdfunding in Indonesia) - Putu Yani Pratiwi; Ika Yanuarti; Wim Prihanto (ADI Publisher, 2020)
Agriculture crowdfunding is a source of alternative financing for farmers. The crowdfunding platform does not ask collateral from the farmer, hence they apply group lending with joint liability to lower the default risk. The purpose of this paper is to understand how joint liability group lending can lower the risk of both farmers and agriculture crowdfunding. A deductive qualitative research design with case study approach is used in this paper. A series of in depth interviews were conducted with one agriculture crowdfunding and two farmers groups. Data analysis is done by using pattern matching techniques. The findings of this paper are joint liability can lower the default risk of crowdfunding platform because the farmers groups are self selected and all member have strong relationship (peer selection), the leader of the farmers group plays an important role of monitoring the member activities (peer monitoring) and he may apply social sanction to the defaulting member (peer pressure). From the farmer’s side, joint liability can lower the price risk. This can be done because crowdfunding platforms apply group lending, so it can get a high volume of commodities from the farmer. This enables crowdfunding platforms to build B2B contracts with buyer companies and give fixed buying prices to farmers upon contract.